Performance of a Future Spaceborne Water Vapour Lidar - Kiemle, Christoph; Ehret, Gerhard; Wirth, Martin; Fix, Andreas (2014)
Water vapor arguably lies at the heart of most key atmospheric processes. Humidity is essential for the development of severe weather, it influences, directly and indirectly through cloud formation, the planetary radiative balance, and it influences atmospheric dynamics, surface fluxes and soil moisture. Water vapor is the only radiatively important atmospheric constituent that is short‐lived and abundant enough so as to be essentially under natural control. Yet this control endows it with a strong positive feedback on climate changes driven by other influences. The latent heat of water vapor also accounts for roughly half the pole-ward, and most of the upward, heat transport within the atmosphere. Finally, water vapor dominates the net radiative cooling of the troposphere which drives convection. Despite its central importance, research to date has not led to a universally accepted picture of the factors controlling water vapor amount, a solid understanding of the mechanisms by which it influences atmospheric processes, or even precise knowledge of its concentrations in many parts of the atmosphere (Sherwood et al., Rev. Geophys. 2010). Recent advances in laser technology will enable the implementation of differential absorption lidar onboard a satellite to globally observe water vapour. In contrast to passive sounders that typically suffer from coarse vertical resolution and unknown aerosol or cloud biases, active lidar remote sensing is calibration-free and its measurement uncertainties can be precisely quantified and traded-off by adapting the spatial resolution to the particular atmospheric context and to the user needs. Results from a performance study will be presented, showing that a four-wavelength lidar, in operation as an airborne demonstrator at DLR since 2007 (Wirth et al., Appl. Phys. B 2009), will, installed onboard a low-earth orbit platform (500 km), enable water vapour profiling up to a height of 16 km in tropical, mid-latitude and arctic climates, with 1 km vertical and 100 km horizontal ...